2005
DOI: 10.1002/jbm.a.30477
|View full text |Cite
|
Sign up to set email alerts
|

The phase state of NiTi implant material affects osteoclastic attachment

Abstract: In the present work, the responses of mature osteoclasts cultured on austenite and martensite phases of NiTi shape memory implant material were studied. We used the sensitivity of osteoclasts to the underlying substrate and actin ring formation as an indicator of the adequacy of the implant surface. The results showed osteoclasts with actin ring on both NiTi phases. However, significantly more osteoclasts were present on the austenitic NiTi than on the martensitic NiTi. We also analyzed the surface free energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Since martensitic presence is almost unavoidable, any knowledge concerning its effects on cells, tissues, and variations in their environments seems to be important. As previously demonstrated,8 martensite can have adverse effects on bone resorbing osteoclasts in vitro . In this study, we investigated the effect of austenite and martensite Nitinol on fibronectin remodeling and conformation, and also the effect of fibronectin‐Nitinol on osteoblast proliferation and cell cycle.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Since martensitic presence is almost unavoidable, any knowledge concerning its effects on cells, tissues, and variations in their environments seems to be important. As previously demonstrated,8 martensite can have adverse effects on bone resorbing osteoclasts in vitro . In this study, we investigated the effect of austenite and martensite Nitinol on fibronectin remodeling and conformation, and also the effect of fibronectin‐Nitinol on osteoblast proliferation and cell cycle.…”
Section: Discussionsupporting
confidence: 51%
“…When incomplete MT takes place, whatever the reason, two phases above may coexist in material structure, thus, regulating material properties. It has been previously observed that the austenite and martensite phases of Nitinol have a different effect on primary rat osteoclasts 8. On martensite, osteoclast morphology deteriorated and the cells failed to form an actin ring structure.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Bone resorption occurs via tight attachment of osteoclasts onto the target bone area, in which both organic (mainly collagen) and inorganic (hydroxyapatite) bone matrix constituents are dissolved. In non-resorbing osteoclasts actin is arranged at the cell periphery as podosomes, whereas in the resorptive phase active osteoclasts can easily be detected by staining actin; functional osteoclasts form a so-called sealing zone consisting of a ringlike actin structure. …”
Section: Introductionmentioning
confidence: 99%
“…ALP, a precocious marker of osteogenetic differentiation, is found in high quantities in the cells in the phase ofmineralization ofthe matrix, as are the osteoblasts (24). Recent studies have demonstrated that the physical and chemical characteristics of the implant surface influence the adhesion, proliferation, differentiation and maturation of bone celt's (25)(26). The leveling of the alkaline phosphate production probably depends on the fact that the cells had densely colonized the implant surface, creating a phenomenon of metabolic slowing and inhibition.…”
Section: Resultsmentioning
confidence: 99%